Common variable immunodeficiency revisited: normal generation of naturally occurring dendritic cells that respond to Toll-like receptors 7 and 9. (4th February 2014) - Taraldsrud, E; Fevang, B; Aukrust, P; Beiske, K H; Fløisand, Y; Frøland, S; Rollag, H; Olweus, J
Summary: Patients with common variable immunodeficiency (CVID) have reduced numbers and frequencies of dendritic cells (DCs) in blood, and there is also evidence for defective activation through Toll-like receptors (TLRs). Collectively, these observations may point to a primary defect in the generation of functional DCs. Here, we measured frequencies of plasmacytoid DCs (pDCs) and myeloid DCs (mDCs) in peripheral blood of 26 CVID patients and 16 healthy controls. The results show that the patients have reduced absolute counts of both subsets. However, the decreased numbers in peripheral blood were not reflected in reduced frequencies of CD34 + pDC progenitors in the bone marrow. Moreover, studies at the single cell level showed that DCs from CVID patients and healthy controls produced similar amounts of interferon-α or interleukin-12 and expressed similar levels of activation markers in response to human cytomegalovirus and ligands for TLR-7 and TLR-9. The study represents the most thorough functional characterization to date, and the first to assess bone marrow progenitor output, of naturally occurring DCs in CVID. In conclusion, it seems unlikely that CVID is secondary to insufficient production of naturally occurring DCs or a defect in their signalling through TLR-7 or TLR-9.